2014
DOI: 10.1088/1742-5468/2014/09/p09023
|View full text |Cite
|
Sign up to set email alerts
|

Tempered fractional time series model for turbulence in geophysical flows

Abstract: We propose a new time series model for velocity data in turbulent flows. The new model employs tempered fractional calculus to extend the classical 5/3 spectral model of Kolmogorov. Application to wind speed and water velocity in a large lake are presented, to demonstrate the practical utility of the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 25 publications
0
57
0
Order By: Relevance
“…It may be worth exploring the properties of the fractional derivatives of the solar wind time series (e.g., Repperger et al, ) to see if they can provide insight into the noninteger high‐frequency power laws observed in the PSDs. Fractional derivatives of the time series are readily calculated using Fourier transforms (Meerschaert et al, ; Tseng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It may be worth exploring the properties of the fractional derivatives of the solar wind time series (e.g., Repperger et al, ) to see if they can provide insight into the noninteger high‐frequency power laws observed in the PSDs. Fractional derivatives of the time series are readily calculated using Fourier transforms (Meerschaert et al, ; Tseng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that retention of contaminant particles in river beds and eddy pools causes a power-law trailing edge in the concentration profile, which corresponds to (1) with θ = 0 [26,27]. Hence, the model is of the same form as (5), with the left fractional derivative replaced by the right fractional derivative, and hence can be solved by the same method developed in this paper.…”
Section: Problem Formulationmentioning
confidence: 88%
“…We carry out numerical experiments to investigate the performance of the Petrov-Galerkin finite element method for problem (5). We use a uniform space partition with a mesh size h := 1/N .…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…C iw/˛O u.w/, along with its inverse, the tempered fractional integral I˛, u.t/, whose Fourier transform is . C iw/ ˛O u.w/ [6,15,16,[18][19][20]. Because of tempering, the Fourier symbol .…”
mentioning
confidence: 99%